Current Research Impacts in Wireless Sensor Networks - Sasikala, N.; Pavalarajan, S.; Prasanth, A.; Karuppathal, R. (International Journal of Engineering and Technology, 2026)
Wireless Sensor Networks (WSN) play vital role in the present era as it provide effective solution to many application. The potential impacts on scientific research and enormous uses of WSN have drawn incredible attention and hence several researches are emerging regarding WSN. This paper is about to categorize new contributions to various fields of WSN. Various contributions are sorted into four classes as Energy, Routing, Security/Control and Applications. Under each group we precisely describe some of the work done. In routing section we have categorized some of the routing protocols. This paper helps to know about the different research interests in WSN.
Keywords: WSN; Energy; Routing; Security; Applications